Dyskinesia detection and monitoring by a single sensor in patients with Parkinson's disease. Issue 9 (14th July 2015) - Lopane, Giovanna; Mellone, Sabato; Chiari, Lorenzo; Cortelli, Pietro; Calandra‐Buonaura, Giovanna; Contin, Manuela
ABSTRACT Objective In current clinical practice, assessment of levodopa‐induced dyskinesias (LIDs) in Parkinson's disease (PD) is based on semiquantitative scales or patients' diaries. We aimed to assess the feasibility, clinical validity, and usability of a waist‐worn inertial sensor for discriminating between LIDs and physiological sway in both supervised and unsupervised settings. Methods Forty‐six PD patients on l‐dopa therapy, 18 de novo PD patients, and 18 healthy controls were enrolled. Patients underwent clinical assessment of motor signs and dyskinesias and kinetic‐dynamic l‐dopa monitoring, tracked by serial measurements of plasma drug concentrations and motor and postural tests. Results A subset of features was selected, which showed excellent reliability. Sensitivity and specificity of the selected features for dyskinesia recognition were assessed in both supervised and unsupervised settings with an accuracy of 95% and 86%, respectively. Conclusions Our preliminary findings suggest that it is feasible to design a reliable sensor‐based application for dyskinesia monitoring at home. © 2015 International Parkinson and Movement Disorder Society